Integration of bioenergetics in an individual-based model to hindcast anchovy dynamics in the Bay of Biscay. (10th December 2019) - Bueno-Pardo, Juan; Petitgas, Pierre; Kay, Susan; Huret, Martin
Abstract: The population of European anchovy of the Bay of Biscay collapsed at the beginning of the 21st century, causing the closure of its fishery between 2005 and 2010. In order to study both the human and environmental causes of the anchovy population dynamics, an approach coupling individual bioenergetics to an individual-based model was applied between 2000 and 2015. This modelling framework was forced with outputs from a physical–biogeochemical model. In addition to a base-case scenario with realistic forcing, alternative scenarios were run without inter-annual variability in either fishing mortality or environmental conditions. During the decrease in population biomass, a high fishing pressure coincided with a combination of environmental variables promoting the appearance of large individuals that could not survive severe winters because of their high energetic demands. The recovery of the population was favoured by a period of warm years with abundant food favouring the winter survival of age 1 individuals, in coincidence with the closure of the fishery. Our modelling approach also allows to test the consequences of a retrospective implementation of the current harvest control rule from 2000 which, according to our results, would have prevented the collapse of the population and avoided the fishery closure.